DETERMINASI KINERJA PENGELOLAAN PENDAPATAN ASLI DAERAH - Surtikanti Surtikanti; Nanang Suryana (Responsive: Jurnal Pemikiran Dan Penelitian Administrasi, Sosial, Humaniora Dan Kebijakan Publik, 2020)
The objective of this research is identify the effect of job motivation and controling to official of region taxation performance of sukabumi regencies. According to the objective, this research are explanatory research, is done by using survey method. The research was conducted by using method to population of 104 Apparatus at Official of Region Taxation Performance Of Sukabumi Regencies. The samples were taken in the amount of 83 Apparatus based on Slovin method. According to the analysis of the results of data processing the results are that job motivation and controling simultaneously and individually have significantly influence on official of region taxation performance of sukabumi regencies.